Engagement and compliance in education today. (3rd July 2022) - English, Alan
ABSTRACT: Student engagement is one of the most important factors of an effective classroom throughout the P-16 spectrum. Of late, many have attempted to define engagement and establish best practices for maximising it in the classroom. In the process, a number of sources have implied or encouraged a false dichotomy between engagement and compliance. This engagement vs compliance dichotomy is neither supported by current research nor practically applicable to instructors. Here, the author works to briefly define student engagement, discuss what research has thus far indicated about the relationship between engagement and compliance, offer educators suggestions for best practices when pursuing engagement and compliance in the classroom, and suggest what future lines of research could provide useful advancements of knowledge.